3162 Colonization of Pregnant Women with Group B streptococcus in Latin America and Infant Outcomes. (27th March 2019) - HogenEsch, Elena; Haddad, Lisa; Yildirim, Inci; Omer, Saad B
Abstract : OBJECTIVES/SPECIFIC AIMS: The primary objective of this study is to determine the prevalence of maternal GBS colonization and demographic risk factors associated with maternal GBS colonization in Latin America. Secondary objectives include: To determine if there is an association between maternal colonization with GBS and stillbirth or preterm birth in Latin America. To determine the effect of cesarean section (CS) on the incidence of neonatal sepsis with GBS in mothers colonized with GBS. METHODS/STUDY POPULATION: Study Population: Pregnant women who received prenatal care at sites that utilize the Perinatal Information System (SIP) from 1989 through 2015, and were screened for GBS between 35 and 37 weeks of gestation. Maternal exclusion criteria included spontaneous abortion, stillbirth before 35 weeks, and lack of screening for GBS. Methods: Estimated prevalence (and 95% confidence interval) of maternal GBS colonization for the entire data set, by region, and by country. The prevalence data for each country further stratified by maternal age, ethnicity, education, civil status and habitation. Descriptive statistics calculated for each clinical prenatal and clinical perinatal health indicator as well as for each clinical history variable for GBS colonized and non-GBS colonized women. Odds ratios will be calculated for each demographic and clinical risk factor. Fisher's exact tests will be used to test hypotheses about the relationship between maternal GBS colonization and specific perinatal outcomes such as stillbirth or preterm birth. We will use multiple logistic regression models to test the hypotheses about the relationships between demographic variables, maternal GBS colonization and perinatal outcomes. RESULTS/ANTICIPATED RESULTS: Preliminary results: 712, 061 records included in database. 98, 852 records with data for GBS screening. o90.6% White, 7.4% Mixed, 0.6% Black, 0.3% Native Indian, 0.1% Other. GBS prevalence among screened women, 17.5% There was a significant association between maternal GBS colonization and ethnicity (X2 (4, N=97006)=569.901, p<0.01) o Prevalence rates by ethnicity: 20.5% Black, 18.4% White, 15.2% Native Indian, 8.8% Mixed, 3.3% Other. There was a significant association between maternal GBS colonization and age (X2 (4, N=98655)=119.901, p<0.01) o Prevalence rates by age group:. Age ≤ 20 - 15.2%. Age 21-34 – 17.8%. Age ≥ 35 – 19.6% Anticipated results:. GBS positive mothers will have an increased burden of stillbirth and preterm birth compared to GBS negative mothers. Neonates born to GBS colonized mothers who deliver via cesarean section will have a decreased incidence of sepsis compared to neonates born to GBS colonized mothers who deliver vaginally DISCUSSION/SIGNIFICANCE OF IMPACT: There have been no comprehensive studies to date that use the CLAP data to characterize the epidemiology of maternal GBS colonization and GBS disease and the burden of neonatal GBS disease in Latin America. Taking advantage of this unique database, this is the first region-wide study using systematically collected data. Our preliminary analysis indicates that GBS colonization status among pregnant women in Latin America is 17.5%, which is greater than previously reported. While there is evidence that maternal carriage of GBS is associated with stillbirth, this will be the first study to quantify the burden of GBS-associated stillbirth in Latin America. Additionally, previous work has been inconclusive in regards to maternal colonization with GBS and its association with preterm birth. This will be the largest study to evaluate the association of maternal GBS carriage with preterm birth. Findings from this study have the potential to inform public health policy and interventions by identifying the prevalence and risk factors.